2012
DOI: 10.1002/jctb.3975
|View full text |Cite
|
Sign up to set email alerts
|

In situ imaging of biopolymers and extracellular enzymes in activated sludge flocs of a municipal wastewater treatment plant

Abstract: BACKGROUND: The aim of this study was to investigate biopolymers and extracellular enzymes in whole activated sludge flocs originating from a full-scale wastewater treatment plant, by means of confocal laser scanning microscopy (CLSM) techniques. Both sectioned and whole activated sludge floc samples have been stained using specific fluorochromes and immunostains in order to visualize the structural and functional characteristics of these bioaggregates. Samples were stained for visualization of lipids, sugars,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…The prepared bacterial cells were freeze dried for 4 h, subsequently coated with gold‐palladium powder by Sputter Coater (SC‐7625, EMITECH, India) and finally attached on to the microscope supports with silver glue. Scanning electron microscope images were taken at 5 kV using a FE‐SEM (Zeiss, ∑‐Sigma, Germany) . Ninety‐six hours older bacteria were grown upon sterile glass coupons and subjected to atomic force microscope (AFM) for visualizing bacterial cells within biofilm .…”
Section: Methodsmentioning
confidence: 99%
“…The prepared bacterial cells were freeze dried for 4 h, subsequently coated with gold‐palladium powder by Sputter Coater (SC‐7625, EMITECH, India) and finally attached on to the microscope supports with silver glue. Scanning electron microscope images were taken at 5 kV using a FE‐SEM (Zeiss, ∑‐Sigma, Germany) . Ninety‐six hours older bacteria were grown upon sterile glass coupons and subjected to atomic force microscope (AFM) for visualizing bacterial cells within biofilm .…”
Section: Methodsmentioning
confidence: 99%
“…The presence of EPS which have a significant influence on the physicochemical properties of microbial aggregates, such as structure, surface charge, flocculation and settling properties has also been studied using CLSM. Thorough analyses of the structural characteristics of AS flocs and spatial distribution of floc components, showing biopolymers, total cells, bacteria, and enzyme distribution, have already been published [115,116]. In spite of these advantages provided by CLSM, there are several disadvantages pointed out by Daims and Wagner [108].…”
Section: Confocal Laser Scanning Microscopymentioning
confidence: 99%
“…Sectioning was technically difficult due to the fragile structure of the particles. Some previous FISH–CLSM research of sludge flocs and mangrove roots did not adopt sectioning. Szilveszter et al indicated that the CLSM images of sludge flocs without sectioning were similar to those after being sectioned (5 μm), and fluorescent probes penetrated well into the uncut flocs. The reason might be that, unlike biological tissues that are relatively dense and constitute diffusion barriers hindering the penetration of probes, the loose structure of sludge flocs would allow better penetration even though they were not sectioned.…”
Section: Methodsmentioning
confidence: 99%